LITERATURE REVIEW ON THE IMPLEMENTATION OF "SOP" WORK PROCEDURES FOR VALID AND RELIABLE PHYSICAL ABILITY TEST RESULTS - Samsul Arifin; Zamroni; Bambang Subali (Sport Scientific And Practical Aspects, 2025)
The purpose of this literature review is to identify physical ability test procedures to produce valid and reliable tests. The test procedure governs the steps or procedures, relationships between people involved in the work system and assessment. Test procedures generally contain how the planning of a test will be carried out, what and how the activities carried out by testers and testes during carrying out physical ability tests and how to conduct a final assessment or evaluation to decide on a test result. The results of the literature review indicate that in each completion of the work including the physical abilities test it is necessary to have a standard test procedure to be used as a guide for testers and testes in carrying out physical ability tests. To produce valid and reliable measurements and assessments, the absolute tester must follow all instructions, steps, and procedures and must not reduce or even eliminate some of the procedures that have been set.